ANALISIS PENGAKUAN DAN PENGUKURAN PENDAPATAN BAGI HASIL PADA BPRS AL-WASHLIYAH - Jainuddin Ismail; Alistraja Dison Silalahi; Reza Hanafi Lubis; Indra Fauzi (Program Studi Akuntansi Fakultas Ekonomi UMN AL Washliyah, 2022)
The purpose of this study was to determine and analyze mudharabah financing in increasing net income at BPRS Al-Washliyah. To find out and analyze what causes mudharabah financing to decline at Al-Washliyah BPRS. The research design uses descriptive qualitative research methods. The data collection techniques used by the author are through documentation and interviews. Analysis of the data used in this study is to analyze qualitative data consisting of interviews and data from the financial report document of BPRS Al-Wasliyah. From the research results, the recognition of murabahah income is recognized proportionally to the amount of cash that has been successfully collected from murabahah receivables. Mudharabah revenue sharing is recognized on a monthly basis during the period the profit sharing rights occur in accordance with the agreed ratio. Ujrah income is recognized at the time of initial payment (paid in advance) or during the contract period, according to the agreement between the bank and the customer. Recognition of murabahah revenue is recognized in proportion to the amount of cash collected from murabahah receivables. This is in accordance with PSAK No. 102 paragraph 23. Recognition of mudharabah revenue sharing is recognized on a monthly basis during the period the profit sharing rights occur in accordance with the agreed ratio. This is not in accordance with PSAK No. 105 paragraph 22 because the recognition of mudharabah operating income in practice can be known based on the profit sharing report on the realization of operating income from the fund manager. Not allowed to recognize revenue from projected operating results. Recognition of ujrah income is recognized at the time of payment (paid in advance) or during the contract period, according to the agreement between the bank and the customer. This is not in accordance with PSAK No. 107 paragraph 14 because rental income over the term of the contract is recognized when the benefits of the asset have been delivered to the lessee.